A Critical Study of Iskandar Zulkarnain's Thought on 'The Ahmadiyya Movement in Indonesia' from the Phenomenological Perspective of Edmund Husserl - Budiman, Arman (An-Nida', 2023)
Studying the Ahmadiyah movement in Indonesia through the work of Iskandar Zulkarnain, according to researchers, requires a reassessment of the figure to determine whether the history is truly discussed without any intervention from any party or the opposite. This is crucial as it will determine the historical accuracy and reveal whether Ahmadiyah has contributed to the development of Islamic scholarly studies, especially in Indonesia. The method used in this research is library research. The data collection technique relevant to this study is documentary research, which involves various literature related to the thoughts or concepts of the figure under examination. The results of this research conclude that the Ahmadiyah movement entered Indonesia with the departure of three Indonesian youths to India. These three youths were Abu Bakar Ayyub, Ahmad Nuruddin, and Zaini Dahlan, all from Padang Panjang, West Sumatra. In his research on the Ahmadiyah movement in Indonesia, Iskandar Zulkarnain truly used two tools offered by Edmund Husserl, namely epoche and eidetic. Iskandar successfully suspended his initial knowledge to obtain valid information from the Ahmadiyah community, as evidenced by Iskandar Zulkarnain's research. Many historical facts support that Ahmadiyah is appreciated by Muslim intellectuals in the homeland. Through the Islamic works written by Indonesian figures, it can be traced that there are indications that their ideas are inspired by the literature of Ahmadiyah figures, especially in the narrative of comparative religion and Christology. With this evidence, it can be concluded that Ahmadiyah's ideas are visualized in many intellectual works by Indonesian Muslim figures.Abstrak: Mengkaji gerakan Ahmadiyah di Indonesia melalui karya Iskandar Zulkarnain menurut peneliti perlu adanya tinjauan ulang terhadap tokoh (peneliti), apakah benar-benar mengulas sejarah tanpa adanya intervensi dari kalangan manapun atau malah sebaliknya. Hal ini sangat penting, sebab akan menentukan kebenaran sejarah dan pengungkapan apakah Ahmadiyah memiliki kontribusi dalam perkembangan pengkajian keilmuan Islam khususnya Indonesia. Metode yang digunakan dalam penelitian ini adalah penelitian  (library research). Teknik pengumpulan data yang relevan dengan penelitian ini adalah studi dokumentasi, studi dokumentasi mengarah kepada berbagai macam literatur yang berhubungan dengan pemikiran atau konsep tokoh yang dikaji. Hasil dari penelitian ini menyimpulkan bahwa gerakan Ahmadiyah masuk ke Indonesia dimulai dengan berangkatnya tiga orang pemuda Indonesia ke India. Ketiga pemuda itu adalah Abu bakar Ayyub, Ahmad Nuruddin dan Zaini Dahlan, ketiganya berasal dari Sumatera Barat Padang Panjang. Dalam penelitiannya tentang gerakan Ahmadiyah di Indonesia Iskandar Zulkarnain benar-benar menggunakan dua alat yang ditawarkan oleh  Edmund Husserl, baik itu epoche dan eiditic. Iskandar berhasil menanggalkan pengetahuan awalnya demi mendapatkan informasi yang valid dari jemaah Ahmadiyah, terbukti melalui riset Iskandar Zulkarnain, banyak fakta-fakta sejarah yang mendukung Ahmadiyah diminati oleh intelektual muslim tanah air. Melalui karya keislaman yang ditulis oleh tokoh asal Indonesia, dapat dilacak adanya indikasi bahwa ide karya mereka terinspirasi dari literatur milik tokoh Ahmadiyah, terutama dalam narasi perbandingan agama dan kristologi. Cukup dengan bukti ini, bahwa ide Ahmadiyah tervisualisasikan dalam banyak karya intelektual muslim asal Indonesia.